Survival of dental implants and intra and postoperative complications in maxillary sinus lift with lateral window and simultaneous dental implant in ridges with severe resorption - Jiménez Castellanos, Fabio Andrés (2020)
Aim: The positioning of dental implants simultaneous to the elevation of the maxillary sinus in ridges with severe bone resorption (≤4mm) is a surgical technique that reduces operative times. However, it is considered sensitive, being dependent on the operator, and in the absence of appropriate handling, complications can occur. This study aimed to provide a review of the literature on the survival of dental implants and intra- and post-operative complications in maxillary sinus lift procedures with the simultaneous placement of a dental implant in ridges with severe bone resorption. Materials and methods: A bibliographic search of the literature published in the last 10 years in the Medline-Pubmed, EBSCO HOST and SCOPUS databases was carried out from May to June 2019. This was complemented with a manual search in journals specialized in Periodontology and Oral Surgery Q1, positioned in the Top 5 of the year 2018 at www.scimagojr.com. Prospective, retrospective and clinical trials were included 2562. A total of 2562 prospective, retrospective and clinical trials were included. After analyzing the titles and reading the abstractsand full texts, 6 articles were selected for analysis of the surgical technique and 35 to complement information. Conclusions: The placement of dental implants simultaneously with maxillary sinus elevation is one of the techniques used to restore function in the posterior maxilla. The most frequent intra-operative complication is perforation of the sinus membrane, and the most common postoperative complication is infection associated with perforation of the membrane, or migration of the implant to the maxillary sinus. The average implant survival reported is greater than 94%.